Electron Confinement at the Si/MoS2 Heterosheet Interface. Issue 10 (23rd February 2016) - Molle, Alessandro; Lamperti, Alessio; Rotta, Davide; Fanciulli, Marco; Cinquanta, Eugenio; Grazianetti, Carlo
Abstract : The electronic band line‐up between a uniform 2D silicon layer and a MoS2 substrate is shown to result in a distortion of the MoS2 bands. This effect is reflected in the admittance and electrical transport responses measured from the field‐effect transistor incorporating the Si/MoS2 heterosheet interface and fabricated from MoS2 multilayer flakes on SiO2 /Si ++ substrates. In particular, the gate modulation of the capacitance curve and the observation of a double‐peak feature in the transconductance profile make evidence of the built‐in of two active channels in the transistor: one at the MoS2 /SiO2 interface and the other at the Si/MoS2 heterosheet interface. The emergence of a gate modulated conductive channel at the Si/MoS2 heterosheet interface is rationalized in terms of an effective electron accumulation at the Si/MoS2 interface that is consistent with the electronic band bending deduced from high‐resolution synchrotron radiation photoemission spectroscopy. Abstract : A 2D silicon layer epitaxially grown on MoS2 is shown to result in a distortion of the MoS2 electronic bands in the proximity of the interface. This effect is responsible for the electron accumulation at the Si/MoS2 heterosheet interface which gives rise to an additional gate modulated electronic channel in the transistor response.